Tactics of cardiosurgical patients with concomitant stenotic lesions of carotid arteries - Matyash, A.; Bondar, L.; Fedko, V.; Krykunov, A. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The combination of cardiac surgery and carotid artery disease requires more attention and understanding in tactics for the management of such patients. Treatment of cardiac surgery with the use of artificial blood circulation or the technique of intervention on the working heart, in these patients, without correction of damage to the carotid arteries, is dangerous and can lead to a stroke. In patients with asymptomatic stenosis of carotid arteries after cardiac surgery, the incidence of stroke is 3%, due to improper blood supply to the brain. The combination of carotid stenosis with cardiac surgery causes a number of questions regarding the definition of optimal tactics for the management of such patients. A group of patients was 18 patients who had a combination of cardiac surgery with different variants of hemodynamic and significant narrowing of the carotid arteries. All patients were examined and surgically treated. Carotid endarterectomy was performed in all cases, but it was carried out at once or in stages, depending on the severity of the cardiological pathology. A special approach is to choose disaggregation and anticoagulation therapy. In the early postoperative period, all patients were assigned low molecular weight heparins and Clopidogrel 75 mg. In connection with implantation of artificial valves, Warfarin was prescribed (target value of MNO 2.5-3.0).